Three-Dimensional Crossbar Interconnection Using Planar-Integrated Free-Space Optics and Digital Mirror-Device - Limmer, Steffen; Fey, Dietmar; et al. (Optoelectronic Integrated Circuits XIII (Proceedings Volume), 2011)
We consider the implementation of a dynamic crossbar interconnect using planar-integrated free-space optics (PIFSO) and a digital mirror-device™ (DMD). Because of the 3D nature of free-space optics, this approach is able to solve geometrical problems with crossings of the signal paths that occur in waveguide optical and electrical interconnection, especially for large number of connections. The DMD device allows one to route the signals dynamically. Due to the large number of individual mirror elements in the DMD, different optical path configurations are possible, thus offering the chance for optimizing the network configuration. The optimization is achieved by using an evolutionary algorithm for finding best values for a skewless parallel interconnection. Here, we present results and experimental examples for the use of the PIFSO/DMD-setup.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD3.threed
Keywords: Crossbar networks; Evolutionary algorithm; High density I/O; Integrated free-space optics; MEMS; Modeling and simulation; Optical interconnection; Optimization; Parallel computing